The Role of Microcredit in Promoting Women’s Entrepreneurship Skills: Lesson from Amanah Ikhtiar Malaysia (AIM), Malaysia (Journal of Governance and Development (JGD), 2015)
Some scholars’ view of microcredit’s potential as a tool of women’s involved in a globalized capitalist economy. It seems that this scheme create opportunities for women to get involve in the entrepreneurship programme. In the case of Malaysia, AIM’s microcredits programs is an individual-based lending, and a near exclusive focus on women as loan clients, have become platform to produce entrepreneur as well as antipoverty intervention. Microcredit aims to break the rural poor in developing countries especially groups of unable to access bank loans and poor villagers rely on local moneylenders. For these people, microcredit provides an alternative source of credit and offering collateral-free loans. Previous studies shown that microcredit has changed the socio-economic of the participant in increasing empowerment, entrepreneur skills, transformational thinking and a desire to improve get out from poverty. The finding presented here provided the empirical evidence and augment previous research on the factor role of microcredit in promoting women’s entrepreneurship skills and the effectiveness of AIM in encourage women to venture into the world of entrepreneurship.